2009
DOI: 10.2737/fpl-rp-655
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a borax-copper preservative in exposed applications

Abstract: This publication is also available online at www.fpl.fs.fed.us. Laboratory publications are sent to hundreds of libraries in the United States and elsewhere. The Forest Products Laboratory is maintained in cooperation with the University of Wisconsin. The use of trade or firm names in this publication is for reader information and does not imply endorsement by the United States Department of Agriculture (USDA) of any product or service. The USDA prohibits discrimination in all its programs and activities on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The sodium silicate addition to BC appeared to lessen the extent of surface discoloration to some extent but this was difficult to evaluate in later stages of the study because of decay development. Comparison of decay development in decking in this study to that of Mississippi in-ground stake specimens from an earlier report (Lebow et al 2009) shows the great difference in decay hazard between the types of exposure and exposure locations (Table 5). For example, decay was not detected in any decking specimens treated with 2,34 % BC until year 18, while this condition was reached within the first year in the Mississippi stake exposure.…”
Section: Bc Deckingmentioning
confidence: 58%
See 4 more Smart Citations
“…The sodium silicate addition to BC appeared to lessen the extent of surface discoloration to some extent but this was difficult to evaluate in later stages of the study because of decay development. Comparison of decay development in decking in this study to that of Mississippi in-ground stake specimens from an earlier report (Lebow et al 2009) shows the great difference in decay hazard between the types of exposure and exposure locations (Table 5). For example, decay was not detected in any decking specimens treated with 2,34 % BC until year 18, while this condition was reached within the first year in the Mississippi stake exposure.…”
Section: Bc Deckingmentioning
confidence: 58%
“…Permanence of the boron and copper in the treated wood is a consideration and it is expected that the type of outdoor exposure (above-ground versus ground-contact) will affect both efficacy and permanence. Stake tests installed in Mississippi and Wisconsin indicated that BC does not provide adequate protection at the concentrations evaluated (Lebow et al 2009). Failures were particularly rapid at the Mississippi test site and appeared to be associated with boron depletion and subsequent colonization by copper-tolerant fungi.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations